IS TOCILIZUMAB AN EFFECTIVE THERAPY FOR SEVERE COVID-19: A SINGLE CENTER STUDY - Sarfaraz, Samreen; Shaikh, Quratulain; Iftikhar, Sundus; Herekar, Fivzia; Saleem, Syed Ghazanfar; Kanani, Fatima (Journal of Ayub Medical College Abbottabad, 2022)
Background: The quest for effective therapies in Covid-19 continues. We compared the outcome of severe COVID-19 patients treated with and without Tocilizumab, an IL-6 inhibitor. Methods: This is a prospective cohort study on the clinical characteristics and outcomes of patients with Covid-19 patients admitted at The Indus Hospital and Health Network, Karachi between 24th March and 19th June 2020. Adult patients who received TCZ were compared with respect to mortality and days of hospitalization with those who did not. Results: A total of 88 patients including 41 patients in the TCZ group and 47 in non-TCZ group were recruited. Baseline demographic characteristics were comparable. TCZ group patients presented with worse clinical features including median SpO2 82% vs 88%, p<0.05 and CRP 193 vs 133.9 mg/L, p<0.05. Approximately, 85.4% were admitted in ICU compared to 69.8% in non-TCZ group, p>0.05. Mortality was not different among the groups (46% in TCZ group vs 51.1% in non-TCZ group, p>0.05). Median length of hospital stays, days of intubation, use of inotropic agents, and use of invasive ventilation or in-hospital complications were similar between the groups. Sub-group analysis revealed that mortality within TCZ group was associated with high IL-6 levels (173 vs 69.66 pg/ml, p<0.05), ICU admission (100% vs 72%, p<0.05), need for mechanical ventilation (100% vs 13.6%, p<0.05) and higher incidence of in-hospital complications, p<0.05. Conclusion: TCZ failed to demonstrate any mortality benefit in our patients. Non-survivors within the TCZ group were more critical compared to survivors and developed more in hospital complications.